2011
DOI: 10.3892/ijmm.2011.761
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 activation diminishes during adipocyte differentiation of ST2 cells

Abstract: Abstract. Adipocyte differentiation (adipogenesis) is a highly controlled process known to be affected, among other factors, by the redox status of the cell. Nrf2 (NFE2-related factor 2) is a transcription factor that orchestrates the expression of a battery of antioxidant and detoxification genes under both basal and stress conditions. The present study investigated the activation of Nrf2 during adipocyte differentiation using as a model the mouse bone marrow-derived ST2 cell line. Treatment of ST2 cells with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“… 45 The protein level of nuclear Nrf2 also continuously decreases during adipogenic differentiation in ST2 cells, a bone marrow-derived MSC cell line. 46 This expression pattern is required for normal adipocyte differentiation of 3T3L1 cells and is associated with increased oxidative stress levels that can facilitate differentiation processes. 47 SFN can also suppress the adipogenic differentiation of 3T3L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“… 45 The protein level of nuclear Nrf2 also continuously decreases during adipogenic differentiation in ST2 cells, a bone marrow-derived MSC cell line. 46 This expression pattern is required for normal adipocyte differentiation of 3T3L1 cells and is associated with increased oxidative stress levels that can facilitate differentiation processes. 47 SFN can also suppress the adipogenic differentiation of 3T3L1 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the differentiation of osteoblasts and adipocytes is tightly regulated and both cell types originate from a common progenitor. Using a cell culture model, Chartoumpekis et al [56] demonstrated that during adipocyte differentiation, Nrf2 activation is decreased. This indirectly supports our finding that upon Nrf2 deletion, osteoblast differentiation was decreased.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Chartoumpekis et al . observed lower NRF2 abundance in the nucleus during adipogenesis, which they hypothesized could lead to the higher ROS levels needed for the differentiation process [125]. …”
Section: Ros Response Mechanisms: Transcription Factorsmentioning
confidence: 99%